Expression analysis of limb element markers during mouse embryonic development. Issue 11 (7th November 2018) - Rafipay, Alexandra; Berg, Amanda L. R.; Erskine, Lynda; Vargesson, Neil
Abstract : Background : While data regarding expression of limb element and tissue markers during normal mouse limb development exist, few studies show expression patterns in upper and lower limbs throughout key limb development stages. A comparison to normal developmental events is essential when analyzing development of the limb in mutant mice models.Results : Expression patterns of the joint marker Gdf5, tendon and ligament marker Scleraxis, early muscle marker MyoD1, and blood vessel marker Cadherin5 (Cdh5) are presented during the most active phases of embryonic mouse limb patterning. Anti‐neurofilament staining of developing nerves in the fore‐ and hindlimbs and cartilage formation and progression also are described.Conclusions : This study demonstrates and describes a range of key morphological markers and methods that together can be used to assess normal and abnormal limb development. Developmental Dynamics 247:1217–1226, 2018. © 2018 The Authors. Developmental Dynamics published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists Key Findings: Expression patterns of molecular markers throughout both fore‐ and hindlimb development ‐ which can be used to assess normal and abnormal development. Detailled description of innervation during fore‐ and hindlimb development confirming innervation first seen after limb patterning events have begun. Description of cartilage development and progression indicates alizarin red staining not seen until E15.5 in both fore‐ and hindlimbs. Hindlimb lags behind forelimb molecularly and morphologically until E14.5. Detailled description of methods used to study fore‐ and hindlimb development.